Solve for y 1.6(3y-2)-1=-8.9+4.8y+4.7

Math
1.6(3y-2)-1=-8.9+4.8y+4.7
Simplify 1.6(3y-2)-1.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
1.6(3y)+1.6⋅-2-1=-8.9+4.8y+4.7
Multiply 3 by 1.6.
4.8y+1.6⋅-2-1=-8.9+4.8y+4.7
Multiply 1.6 by -2.
4.8y-3.2-1=-8.9+4.8y+4.7
4.8y-3.2-1=-8.9+4.8y+4.7
Subtract 1 from -3.2.
4.8y-4.2=-8.9+4.8y+4.7
4.8y-4.2=-8.9+4.8y+4.7
Add -8.9 and 4.7.
4.8y-4.2=4.8y-4.2
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 4.8y from both sides of the equation.
4.8y-4.2-4.8y=-4.2
Subtract 4.8y from 4.8y.
0y-4.2=-4.2
Multiply 0 by y.
0-4.2=-4.2
Subtract 4.2 from 0.
-4.2=-4.2
-4.2=-4.2
Since -4.2=-4.2, the equation will always be true for any value of y.
All real numbers
The result can be shown in multiple forms.
All real numbers
Interval Notation:
(-∞,∞)
Solve for y 1.6(3y-2)-1=-8.9+4.8y+4.7

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top